Analysis of The Need for Gamification of “Gamasura” for Understanding Local Culture In The Teaching of Pancasila Education on Cultural Diversity for Fifth Grade Elementary School Students - Rifka Anisa Ummami; Ratri Cahyaning Asri; Zaenal Abidin (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2025)
The issue of low understanding of local culture among elementary school students is a crucial concern for maintaining national identity. The purpose of this study is to analyze the need for GAMASURA gamification for the understanding of local culture among fifth-grade elementary school students. This research was conducted at SDN Sambikerep II/480 Surabaya. The participants in this study were 20 fifth-grade elementary school students. The method used was a questionnaire on the need for GAMASURA gamification. The results of this study show that all fifth-grade students at SDN Sambikerep II/480 Surabaya have digital devices for learning and use digital applications for learning. As many as 75% of students stated that they were interested in learning about the diversity of Indonesian culture. In addition, as many as 55% of students were interested in learning while playing with game elements, as many as 45% of students considered that the use of game elements in learning was very interesting, and as many as 60% of students thought that quiz games were the most popular type of game in learning. Therefore, learning using GAMASURA gamification is needed. The conclusion of this study is that there is a need to develop learning media in the form of GAMASURA gamification for the subject of “Indonesian Cultural Diversity” for fifth-grade elementary school students.